(untitled) (Lex Scientia Law Review, 2025)
The United Nations Convention on the Law of the Sea (UNCLOS) provides a comprehensive legal framework for protecting and preserving the marine environment, including coastal areas. This study examines the application of international legal regulations regarding coastal conservation and jurisdictional management of coastal lands between Indonesia and Malaysia in the digital era. Employing a normative and qualitative approach, the research analyzes secondary data from legal materials of both countries, using a comparative method to identify similarities, differences, and points of convergence between their legal systems. In Indonesia, digital transformation by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has enhanced transparency and efficiency in land management; however, policy adjustments are still needed for effective coastal ecosystem protection. Meanwhile, Malaysia, with its long and erosion-prone coastline, has implemented various laws and policies, including Coastal Zone Management (CZM), to address issues such as erosion and pollution. Although both countries face similar challenges and opportunities, their approaches differ. Indonesia needs to optimize its policies to effectively protect coastal ecosystems, while Malaysia requires adjustments in implementing its existing laws and policies. Challenges such as overlapping jurisdictional authority, funding limitations, and the need for stakeholder involvement remain significant obstacles. Therefore, successful coastal land management in both countries requires better integration of legal policies, environmental conservation efforts, and digital technology to achieve sustainable outcomes.